(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the current state of knowledge and attitude of salt reduction diet practices of hypertensive patients at Tue Tinh Hospital in 2025 Subjects and methods: A cross-sectional descriptive study of 140 patients who came for examination and treatment at Tue Tinh Hospital who were diagnosed with hypertension during the period from January 2025 to April 2025 Results: Among 140 hypertensive patients, 82.9% knew that table salt affected hypertension, 78.6% knew that instant noodles, ready-to-eat products and pickled foods with high salt content. Attitudes: 54.3% believe that reducing salt intake will support blood pressure control and improve health status; 75% are willing or very willing to change their diet to reduce salt intake. Regarding dietary practice: 52.9% always add dipping sauce; 69.3% do not have the habit of checking food labels when buying processed products. 16.4% of patients have the habit of always using salted products. Conclusion: 55% of hypertensive patients who come to Tue Tinh Hospital for examination and treatment have knowledge about the salt-reducing diet, 72.1% have a positive attitude towards reducing salt in the diet, but only 35.7% are practicing a salt-reducing diet